EFFECT OF POPULATION GROWTH ON THE WATER DUTY OF THE IRRIGATED LANDS WITHIN A PART OF THE CENTRAL DISTRICT OF KERBALA CITY: ALIHNEIDIYAH RIVER AS STUDY CASE - AL-FAWZY, ALI M.; HOMMADI, ALI H.; NAJEM, NAJEM A.; AHMED, HUSSEIN J.; AL-ANSARI, NADHIR A. (Journal of Duhok University, 2023)
The rivers, channels, canals, and other water ways convey and distribute the water to the irrigation field networks. Distribution of water for irrigation purposes subjects to a principle called as "The water duty". This principle is important to satisfy a justified distribution of water for the irrigation projects, and affected by many variables. One of these variables may be the urban growth within the agricultural lands. So, perhaps it needs an annual evaluation to make the water distribution plan on irrigation projects works correctly. The present study views the urban growth that take a place on the green areas which irrigate from a part of AliHneidiyah river in Karbala city, Republic of Iraq, for the distance surrounded by the stations (0+000) and (4+000), to choose between keeping up the current water duty or re-calculate it depending on the last change in space of the green zone within the studied area. The cadastral maps and satellite images are used to determine the areas irrigated from the river inside the study area, and the change that happens in the nature use of these areas. The results of this study shows that the urban growth has an inverse proportion to the green zones, and that impose to modify the water duty calculated and water shares to keep an equalibirium status during the scarcity seasons.